2010
DOI: 10.1007/s10479-010-0724-z
|View full text |Cite
|
Sign up to set email alerts
|

Water supply and consumption uncertainty: a conflict-equilibrium

Abstract: This paper addresses the economic efficiency of water production and distribution in a vertical supply chain consisting of a water-provider and a consumer (municipality). The inherent conflicts over stocks and supply costs that emerge among the parties in the water supply chain are modeled as a zero-sum stochastic differential game. Consequently, the effects of collaboration and competition are contrasted as well as the application of block pricing and subsidies in overcoming potential conflicts between the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Study [13] developed a spatial water distribution plan that can save cost and time. In 2010, Kogan and Tapiero [14] discussed the economic benefits of two-stage water supply chain by constructing a zero-sum stochastic differential game model. Elala et al [15] talked about the safety of water supply chain and provided practical suggestions for communities, enterprises, and local authorities to realize water supply chain risk management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Study [13] developed a spatial water distribution plan that can save cost and time. In 2010, Kogan and Tapiero [14] discussed the economic benefits of two-stage water supply chain by constructing a zero-sum stochastic differential game model. Elala et al [15] talked about the safety of water supply chain and provided practical suggestions for communities, enterprises, and local authorities to realize water supply chain risk management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to derive water resource, Kondili and Kaldellis [25] developed a decision support system (DSS) to coordinate the conflicts between customers' demand in water supply chain. In 2009, a research [14] analyzed the optimal, respectively, in the minimum commitment and flexibility contract based on a two-stage water supply chain. In 2012, a study [26] demonstrated the optimization modeling approach for the pricing and coordinating schemes of SNWD-ER project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examples of empirical approaches include Ruijs et al (2008), where the water pricing social dimension, particularly the distributional effects of water tariffs, is explored, as well as Gómez-Lobo & Contreras (2003), Komives et al (2005) and Kogan & Tapiero (2010), where the distributive impacts of water subsidy schemes relating to block pricing models are evaluated. Renzetti (2000) and GarciaValiñas (2005), who argue that a two-part tariff with a fixed and a volumetric charge might be a good way to achieve distributional objectives without substantially reducing social welfare, are other relevant contributions to the literature.…”
Section: Water Tariffs' Objectives: the 'Social Concerns' Dimensionmentioning
confidence: 99%
“…Guerra et al [29] and Ozawa et al [30] established a framework that integrated water management, and design and planning of the shale gas supply chain. Kogan and Tapiero [31] addressed the economic efficiency of water production and distribution in a vertical supply chain consisting of a water supplier and a consumer (municipality). The study showed that when the supply variance depends on the supply mean, the effect of uncertainty depends on the intensity of the conflict between the municipality and the water supplier.…”
Section: Water Resource Supply Chain Managementmentioning
confidence: 99%